2015
DOI: 10.4236/ijg.2015.67052
|View full text |Cite
|
Sign up to set email alerts
|

Pb Isotopes Study in Recent Sediments from Paraty Bay (Rio de Janeiro, Brazil): Antropogenic Versus Oceanic Signatures

Abstract: We carried out Pb isotopes studies in sediments from Paraty Bay located in the SE area of the Rio de Janeiro State to discriminate the signature of metal contamination from domestic sewage, industries, shipyards and geogenic sources. The studied samples have been chosen in two sectors of the Bay, including the Paraty area and Juatinga Bay. Sample preparation procedures included: 1) drying and granulometric separations (200 mesh); 2) weighting; 3) complete dissolution and 4) Pb isotope analysis obtained by MC-I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 14 publications
0
9
0
Order By: Relevance
“…Lead tends to adsorb on organic debris and be stored within sedimentary deposits in a form that can be released back in the water. 2125 Taking this into account, we correlated our results with Pb isotopic data reported for marine sediments from the same study, and results were plotted together with Pb isotopic data reported for marine sediments from Ilha Grande, 54 Paraty, 52 and Sepetiba Bay 53 (Fig. 7).…”
Section: Resultsmentioning
confidence: 70%
See 2 more Smart Citations
“…Lead tends to adsorb on organic debris and be stored within sedimentary deposits in a form that can be released back in the water. 2125 Taking this into account, we correlated our results with Pb isotopic data reported for marine sediments from the same study, and results were plotted together with Pb isotopic data reported for marine sediments from Ilha Grande, 54 Paraty, 52 and Sepetiba Bay 53 (Fig. 7).…”
Section: Resultsmentioning
confidence: 70%
“…Three isotopes plot showing the results found in shells together with Pb isotopic data reported for surface marine sediments from Ilha Grande Bay, Paraty, and Sepetiba Bay. 52–54 Error bars on the laser ablation analyses are ± 2 standard error of the mean of 40 integration cycles.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The Pb isotopic variations in the air at the specific sites, which are strongly influenced by the Pb emissions from leaded gasoline, will therefore be determined by the market-share of the different alkyl-lead retailers. , As shown in Figure , the 206 Pb/ 207 Pb ratios at Dome Fuji and Dome A show a similar trend moving toward more radiogenic values when the EFs peaked between the mid-1970s and the early 1980s. The 206 Pb/ 207 Pb ratio of gasoline used in Brazil was a relatively radiogenic value of ∼1.2, indicating the predominant use of alkyl-lead additives manufactured from the highly radiogenic Mississippi Valley type Pb in Brazil . In contrast, leaded gasoline in Argentina and Chile was characterized by a relatively low 206 Pb/ 207 Pb ratio (∼1.06), because of the primary use of alkyl-lead supplied by Associated Octel, despite the fact that different alkyl-lead mixtures were supplied to different cities. ,, Consequently, the increasing 206 Pb/ 207 Pb ratios from the mid-1970s to the early 1980s could be considered to support the hypothesis that the large increase in the EFs in the snow during the corresponding period is primarily due to the large emissions of Pb originating from the combustion of leaded gasoline in Brazil.…”
Section: Resultsmentioning
confidence: 99%
“…In Argentina and Chile, the use of Pb additives in gasoline was completely phased out in 1997 and 2001, respectively (Tchernitchin et al 2006, Oudijk 2010. In contrast, leaded gasoline in Brazil was characterized by a relatively high 206 Pb/ 207 Pb ratio because of its primary use of Mississippi Valley type Pb (Bollhofer and Rosman 2000, Bollhofer and Rosman 2002, Munõz et al 2004, Geraldes et al 2015. Because the ban on leaded gasoline in Brazil started in 1975 and leaded gasoline was phased out in the 1980s, this relatively radiogenic signature of Hercules Névé snow dated 2009-2012 was presumably due to Pb emissions from industrial sources Suttie 1994, Paoliello andCapitani 2005).…”
Section: Comparison Of Reported Data With Previous Antarctic Researchmentioning
confidence: 99%